Kinematic analysis of the "attack to the legs"; from wrestling: impact of prior judo expertise - Moufti, H.; Arfaoui, A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Background and Study Aim: In the framework of motor skill learning and transfer, the objective of the present work is to highlight the kinematics during the technical execution of an "attack to the legs" in wrestling and compare expert wrestlers with wrestlers having a prior judo expertise. Moreover, this study aims to evaluate the effects of training on these characteristics. Material and Methods: 10 male subjects were divided in two groups of five: the first group contains wrestlers with at least 7 years of wrestling practice. The second group contains two-year practice wrestlers with 5-year prior judo experience. Subjects had to perform a movement of attack towards the opponent`s legs (free style wrestling). A three-dimensional analysis was carried, the displacement of seven passive markers placed over anatomical points was quantified (3-D motion analyzer, sampling rate 25Hz). The following parameters were calculated: angulation of the hip and of the knee, velocity and acceleration of the shoulder and of the wrist. The experiment was conducted twice: at the beginning of the wrestling training schedule and ten weeks later. Results: Results showed marked differences between the two groups in the kinematics of the movement. These results suggest interference between prior automatisms and learning new skill. The prior experience in judo would have influenced posture in this group. In the framework of skill transfer and dexterity, this study appears promising to investigate the processes involved in this motor control. Conclusions: Although wrestling and judo are two sport disciplines that belong to the same group of combat sport, this work underlines the specificity of learning and indicates that acquisition of motor abilities in a speciality is not transferred inevitably in a positive way in another speciality of the same group